Regional and landscape conservation of Ukraine’s historical parks - Popovych, Serhii; Zibtseva, Olha (Ecological Questions, 2026)
With the passage of time, the understanding of ancient phenomena of nature and culture becomes more relevant. The purpose of the article is to analyze the modern network of ancient protected parks in Ukraine, which are over 100 years old. The modern network is represented by eight botanical gardens, 11 dendrological parks, three zoological parks, and 68 Park Monuments of Landscape Architecture. The density of park distribution varies according to the physico-geographical zones and mountainous regions of Ukraine. Four objects are represented in the mixed forest zone, 21 in the broad-leaved forest zone, 38 in the forest-steppe zone, nine in the steppe zone, seven in the Carpathian mountainous region, and 10 in the Crimean mountainous region. Among the 27 administrative regions, the Autonomous Republic of Crimea leads in terms of quantity and area. The total area of the objects is 1152.80 ha. The diversity of landscapes in the Forest-Steppe and broad-leaved forest zones proved to be the most optimal for ancient park construction. The landscape organization of park territories is modeled by polyfunctional zoning, which is eco-balanced in terms of the distribution of natural and cultural values, eco-conditions, management elements, and conservation regimes. Given the importance of each functional zone and sub-zone, guidelines for their areas are recommended. The strict protection zone should make 10-15% of the total park area, the scientific zone 15-25%, the administrative and economic zone - 5%, and the exhibition zone - 75-50%. A system of architectural and planning organization techniques and conservation regimes.